2016
DOI: 10.1002/adma.201603269
|View full text |Cite
|
Sign up to set email alerts
|

Organic Planar Heterojunctions: From Models for Interfaces in Bulk Heterojunctions to High‐Performance Solar Cells

Abstract: Recent progress regarding planar heterojunctions (PHJs) is reviewed, with respect to the fundamental understanding of the photophysical processes at the donor/acceptor interfaces in organic photovoltaic devices (OPVs). The current state of OPV research is summarized and the advantages of PHJs as models for exploring the relationship between organic interfaces and device characteristics described. The preparation methods and the characterization of PHJ structures to provide key points for the appropriate handli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 396 publications
(493 reference statements)
1
77
0
Order By: Relevance
“…Thermal treatment at 150 °C for 20 min increased J sc to 2.57 mA cm −2 and PCE to 0.49%. [81] More recently, the same group has reported the synthesis of another series of parent "double-cable" polymers with poly(DTBDT) as supporting backbone and pendant PBI acceptor groups (10). [79] The degree of polymerization estimated from 1 H NMR data was limited to 3-4 units.…”
Section: "Double-cable" Polymers With Nonfullerene Acceptor Unitsmentioning
confidence: 99%
“…Thermal treatment at 150 °C for 20 min increased J sc to 2.57 mA cm −2 and PCE to 0.49%. [81] More recently, the same group has reported the synthesis of another series of parent "double-cable" polymers with poly(DTBDT) as supporting backbone and pendant PBI acceptor groups (10). [79] The degree of polymerization estimated from 1 H NMR data was limited to 3-4 units.…”
Section: "Double-cable" Polymers With Nonfullerene Acceptor Unitsmentioning
confidence: 99%
“…[12] There have been substantial advances in understanding the mechanism of OPVs.I th as been shown that the properties of the organic interfaces strongly affect the charge separation and recombination processes. [23][24][25][26] Taken together,t hese studies suggest that precise control of the BHJ structure at the molecular level could be crucial to improving the performance of OPVs further.T he interfacial structures of mixed BHJs,however,are difficult to analyze at the molecular scale because of the limitations of analytical methods. [14][15][16][17][18][19] Therefore,t he spatial arrangement of the donor and acceptor can strongly affect the photophysical and electronic processes in OPVs,a s suggested by theoretical calculations [20][21][22] and experimental studies using planar heterojunctions as model systems.…”
mentioning
confidence: 93%
“…[13] Thec hargetransfer (CT) state at the interface has as trong correlation with the OPV performance. [23][24][25][26] Taken together,t hese studies suggest that precise control of the BHJ structure at the molecular level could be crucial to improving the performance of OPVs further.T he interfacial structures of mixed BHJs,however,are difficult to analyze at the molecular scale because of the limitations of analytical methods. [23][24][25][26] Taken together,t hese studies suggest that precise control of the BHJ structure at the molecular level could be crucial to improving the performance of OPVs further.T he interfacial structures of mixed BHJs,however,are difficult to analyze at the molecular scale because of the limitations of analytical methods.…”
mentioning
confidence: 93%
“…[1][2][3][4][5][6] However, there are some drawbacks that should be overcome in order to utilize them in a wider context including stability (chemical, thermal, photo), solubility, poor optical performance (low quantum yields, low lifetime) due to aggregation. Photoactive, p-conjugated chromophores have many important applications in the areas of sensing, catalysis, lasers, imaging, theranostics and photonics.…”
Section: Introductionmentioning
confidence: 99%